1983
DOI: 10.1073/pnas.80.15.4752
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic resistance to the lethal effects of x-irradiation in insect and arachnid cells

Abstract: Twelve cell lines representing 10 genera of three orders (Diptera, Lepidoptera, and Orthoptera) of the class Insecta and one cell line (Acarina) from the class Arachnida were examined to discern their sensitivity to the lethal effects of x-irradiation. Radiosensitivity was measured by a combination of colony formation and population growth curve techniques. Each of these arthropod cell lines is significantly more radioresistant than mammalian cells, though the degree of resistance varies greatly with order. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…But huge differences exist between mammalian and arthropod cells that must be taken into account before any comparison of biological effectiveness of different energy radiations among such studies. Dipteran cells are 3 to 9 times and lepidopteran cells 52Ð104 times more radioresistant than mammalian cells to X radiation (Koval et al 1978(Koval et al , 1979Koval 1983) and radiosensitivity also decreases with age in insects.…”
Section: Discussionmentioning
confidence: 99%
“…But huge differences exist between mammalian and arthropod cells that must be taken into account before any comparison of biological effectiveness of different energy radiations among such studies. Dipteran cells are 3 to 9 times and lepidopteran cells 52Ð104 times more radioresistant than mammalian cells to X radiation (Koval et al 1978(Koval et al , 1979Koval 1983) and radiosensitivity also decreases with age in insects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the discovery of Mdm2-p53, a key regulator of cell cycle control, may shed light on the mechanisms of increased resistance to radiation in arachnids. 20 of one of the Deer Tick proteins to the recently identified p53 delta isoforms. The common position for the start of translation of the Tick, Human and Zebrafish proteins strongly support the concept that such an N-terminally deleted p53 protein can have a distinct biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the comparative studies revealed that the degree of radioresistance varies greatly from one insect group to the other. Among the different taxonomic groups of insects, lepidopterans (butterflies and moths), orthopterans (cockroaches and grasshoppers) and hemipterans (true bugs) are noteworthy as radiation-resistant insect orders (O'Brien and Wolfe 1964, Koval 1983a, 1983b, Chandna et al 2004. Within these insect orders, radiation threshold doses vary widely, ranging from 1000-2000 Gy.…”
Section: Introductionmentioning
confidence: 98%